The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1080/15622975.2018.1492736
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy of adjustment disorder: A review

Abstract: The work done has been useful insofar as it provides clinicians with some insights into the advantages and disadvantages of a number of pharmacotherapy options. Additional rigorously designed trials are needed to further advance the field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 36 publications
(41 reference statements)
0
11
0
Order By: Relevance
“…Psychotherapeutic and psychopharmacological treatment options for AD have recently been summarized in three review articles (Domhardt and Baumeister, 2018;O'Donnell et al, 2018;Stein, 2018). They found that the quality of evidence has been ranked low to very low (O'Donnell et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychotherapeutic and psychopharmacological treatment options for AD have recently been summarized in three review articles (Domhardt and Baumeister, 2018;O'Donnell et al, 2018;Stein, 2018). They found that the quality of evidence has been ranked low to very low (O'Donnell et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment options include the use of benzodiazepines (alprazolam, diazepam, clorazepat, lormetazepam), antidepressants (mianserin, tianeptine, trazodone, viloxazine), plant extracts/ herbals (euphytose, Ginko-Biloba, Kava-Kava), anxiolytics (etifoxine), 5-HT1A agonists (buspiron), and neutraceuticals (s-adenosylmethionine). However, only 11 randomized-controlled trials including 1,195 AD patients have been documented, yielding in part contradictory results (Stein, 2018). Furthermore, psychopharmacological treatment may be limited by drug-induced side effects, including pharmacokinetic and pharmacodynamics alterations such as drug-drug interactions, induction/inhibition of the cytochrome-P-450 system, or indirect drug effects that all may interact with the drugs necessary for treating the underlying disease (Huang et al, 2008;Kahl, 2018;Kahl et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…They also highlight the good tolerability profile of etifoxine, particularly its preservation of cognitive function and vigilance. Moreover, etifoxine is not associated with either rebound anxiety or withdrawal symptoms following treatment cessation 60…”
Section: Anxiolytic Activity Of Etifoxine: Clinical Trials and Practicementioning
confidence: 95%
“…Controlled (but mostly small) trials in adjustment disorders exist with benzodiazepines for short-term anxiolysis (notably, alprazolam, lorazepam, or diazepam) and sleep aids (especially trazodone). 3 Apart from performing clinical assessments as described above, the fundamental treatment foci of crisis work involve helping people (a) manage immediate physical or emotional distress by providing verbal support, education, skills, and targeted pharmacotherapies when appropriate and (b) identify and implement strategies to better cope and solve tangible problems. "Distress" from crises commonly entails anxiety, agitation, insomnia, preoccupation, grief, feared loss of health, and isolation/loneliness.…”
Section: Pandemic Adjustment Disordersmentioning
confidence: 99%